Partisan Fiscal Policy: Evidence from Central and Eastern Europe - Ondrej Schneider (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper examines effects of political ideology of a governing party on fiscal outcomes, using data from eight Central and Eastern European countries in the 2001-2017 period. The analysis shows that there is a statistically significant effect of conservative governments on fiscal variables, namely they tend to reduce expenditures and improve fiscal balance by 0.4-0.7% of GDP. Conservative governments are found to reduce expenditures on social security and health care, but they tend to increase subsidies. This may be explained by their proximity to business interests that typically benefit from these subsidies. Our result suggest that while conservative governments do tend to reduce public spending and run smaller deficits, their impact on fiscal outcomes is more limited than they often claim.
Keywords: E62; H10; H50; H62; 330; fiscal policy; political parties; budget deficit; European Union